2022
DOI: 10.5206/cjsotlrcacea.2022.1.13588
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perspectives on UDL: Exploring Bridges and Barriers for Broader Adoption in Higher Education

Abstract: Universal Design for Learning (UDL) strategies aim to reduce learning barriers in the classroom for all students and remove the need for students with disabilities to advocate on their own behalf. Leadership in Scholarship of Teaching and Learning has a role to play in advancing inclusive learning cultures in higher education. At the frontline of higher education delivery, faculty are best positioned to implement UDL practices. Initiatives to encourage broader implementation of UDL require an understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In relation to faculty members, they are best placed to implement inclusive practices, although they require a thorough understanding of the barriers and opportunities present in the university (Hills et al, 2022). Studies such as González and Colmenero (2021) agree with the testimonies of faculty members in this systematic review, stating that they carry out inclusive educational processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to faculty members, they are best placed to implement inclusive practices, although they require a thorough understanding of the barriers and opportunities present in the university (Hills et al, 2022). Studies such as González and Colmenero (2021) agree with the testimonies of faculty members in this systematic review, stating that they carry out inclusive educational processes.…”
Section: Discussionmentioning
confidence: 99%
“…Products and environments should be designed to be used by all, without the need for adaptation or specific design (Preiser & Smith, 2011). Universal Design for Learning (UDL) can contribute to a more accessible learning environment by planning subjects for all learners, and considering multiple forms of expression, representation and engagement (Hills et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of the UDL framework can vary greatly among teachers and faculty members, resulting in different levels of complexity and implementation (Ok et al, 2016;Rao and Cook, 2021). Hills et al (2022) found that faculty members recommended enhancing knowledge of UDL and promoting UDL champions as two areas that could boost UDL implementation on campus. Cash et al (2021) emphasized the need for higher education institutions to create a supportive environment that recognizes the importance of implementing inclusive pedagogical techniques and provide relevant training to meet the evolving needs of diverse student learners.…”
Section: Udl In the Library And Across Campusmentioning
confidence: 99%
“…In Higher Education, from this model it is understood that, if a student with a disability cannot access the materials, the resources must be changed (Kumar & Widerman, 2014). UDL is a practical approach that encourages a change in subject design and teaching methods to provide learning opportunities that accommodate all students from the outset (Hills et al, 2022;Seale et al, 2020). This translates into providing multiple means of communication, engagement and expression (Hromalik et al, 2021;Williams et al, 2016).…”
Section: Accessibility To Achieve More Inclusive Practicesmentioning
confidence: 99%